The Influence of Mobile Learning Application Management on Understanding Hadith Material Moderated by Students' Digital Learning Experience - Norman, Efrita (Eduprof : Islamic Education Journal, 2024)
In this digital era, the use of technology, including mobile learning applications, has opened up new opportunities in Islamic education. This study explores the influence of the use of mobile learning applications on the comprehension of Hadith material among students, taking into account moderation by their digital learning experience. This study uses a quantitative approach with a survey research design. The sample consisted of 89 students from the Tarbiyah College of Sciences who used mobile learning applications in learning Hadith. Data collection was carried out through a questionnaire to measure the use of mobile learning applications, digital learning experiences, and understanding of Hadith material.Data analysis showed that the use of mobile learning applications significantly increased the understanding of Hadith material among students. In addition, students' digital learning experiences moderate the relationship between the use of mobile learning applications and Hadith comprehension, with students who have better digital experiences tending to achieve higher comprehension through the app.